The epidemic of thyroid cancer in China: Current trends and future prediction - Wu, Jiayuan; Zhao, Xiaoyan; Sun, Jianzhong; Cheng, Chong; Yin, Chunyu; Bai, Ruhai (Frontiers in Oncology, 2022)
Background Thyroid cancer (TC) is one of the most common cancers in China. The aim of this study was to identify the potential age, period, and cohort effect under the long-term trends in TC incidence and mortality, made projections up to 2030. Methods Incidence and mortality data on TC were obtained from the Global Burden of Disease Study 2019. The population predictions were obtained from the United Nations World Population Prospects 2019. An age-period-cohort model was used for the analysis. Results From 1990 to 2019, the net drift (the overall annual percentage change of TC over time adjusted for age groups) of the TC incidence was 5.01% (95% confidence interval[CI]: 4.72%, 5.29%) for males and 1.48% (95% CI: 1.14%, 1.82%) for females. The net drift of TC mortality was 1.64% (95% CI: 1.38%, 1.91%) for males and –2.51% (95% CI: –2.77%, –2.26%) for females. Regarding the incidence of TC, both the period and the cohort relative risks (RRs) in males and females showed an overall increasing trend. As to the mortality rate of TC, both the period and cohort RRs in females showed a monotonic decline trend. The period RRs for males decreased after 2015, but the cohort RRs revealed a fluctuating upward pattern. From 2019 to 2030, The TC incidence was projected to rise by 32.4% in male and 13.1% in female, the mortality decline by 13.0% in male and 17.3% in female. The elderly was projected to have an increasing proportion of TC occurrence and deaths. Conclusions Over the past 30 years, the incidence rate of TC in China has continually increased, and this trend was projected to continue. Although male mortality has increased in the past, it is expected to decline in the future. The proportion of older people among TC occurrence and death was projected to gradually increase, and the difficulties elderly with TC face require more attention.